Pattern of Follicular Development, CL Size, Steroid Hormones and Biochemical Profile during Early Pregnancy in Heifers and Cows - Hadiya, KK; Dhami, AJ; Lunagariya, PM; Sarvaiya, NP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The follicular development, CL size, plasma progesterone (P4), estradiol-17β (E2), total cholesterol and blood glucose profiles were studied in 6 post-pubertal cyclic heifers and 6 postpartum cyclic cows each of Gir and HF x Kankrej breeds at weekly interval from day 0 (estrus/AI) to day 21 post-AI and then on days 23, 28, 35 and 42 in non-return cases. The mean CL size in heifers (irrespective of breeds) as monitored by transrectal ultrasonography on days 0, 7, 14, 21, 23, 28, 35 and 42 post-AI was found to be 4.72 ± 0.33, 12.30 ± 0.55, 12.72 ± 0.62, 8.74 ± 1.39, 9.47 ± 1.17, 11.83 ± 0.87, 14.44 ± 0.61 and 14.50 ± 0.67 mm, respectively. Plasma P4 concentrations on corresponding days were 0.49 ± 0.10, 3.16 ± 0.21, 5.18 ± 0.41, 3.01 ± 0.99, 3.50 ± 0.96, 5.66 ± 0.73, 8.54 ± 0.21 and 8.96 ± 0.15 ng/ml, respectively. The mean follicular size in heifers on days 0, 7, 14, 21, 23, 28, 35 and 42 post-AI was 12.70 ± 0.51, 5.86 ± 0.52, 5.23 ± 0.45, 9.21 ± 0.96, 7.41 ± 0.91, 6.14 ± 0.48, 4.80 ± 0.51 and 4.94 ± 0.30 mm, respectively. Plasma E2 concentrations on corresponding days were 56.08 ± 2.98, 29.58 ± 2.52, 20.25 ± 2.43, 38.08 ± 5.70, 22.66 ± 4.97, 21.58 ± 2.84, 15.80 ± 2.53 and 22.40 ± 3.29 pg/mL, respectively. Nearly similar values and trend of observations were recorded for CL/follicular size and plasma P4/E2 profile in postpartum cows. The values of CL size and plasma P4 were the lowest, and those of follicle size and plasma E2 were the highest on the day of estrus/AI, changed highly significantly (p <0.01) by day 7 to 14, and again around day 21–23 and fluctuated at or little lower levels around day 35 and 42 post-AI. These trends were associated with recurrence of estrus in few animals around day 21–23, and establishment of pregnancy in others. No significant variation was noted in any of the traits between breeds and between parity at any of the intervals studied. Further, the conceiving and non-conceiving cows (irrespective of breed or parity) revealed identical pattern and values of all 4 traits (CL, Follicle, P4, E2) till day 14 post-AI, and there was significant drop in CL size/P4 and rise in follicular size/E2 profile in non-pregnant animals on day 21 post-AI due to initiation of next cycle. The mean concentration of blood glucose and plasma cholesterol recorded varied from 60.96 ± 1.69 to 68.67 ± 2.10 and 169.79 ± 1.43 to 181.01 ± 1.85 mg/dL, respectively, which did not vary significantly between breeds or intervals post-AI. The values of glucose and cholesterol were non-significantly higher in non-pregnant Gir and pregnant crossbred cattle as compared to their counter parts.